1991
DOI: 10.2737/pnw-rp-439
|View full text |Cite
|
Sign up to set email alerts
|

Veneer recovery of Douglas-fir from the Coast and Cascade Ranges of Oregon and Washington.

Abstract: This file was created by scanning the printed publication. Text errors identified by the software have been corrected; however, some errors may remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…A study conducted by Fahey and Willits (1991) shows that logs with less than 30 cm of diameter should not be peeled. The results in Table 2 confirm the low recovery rate of these assortments.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Fahey and Willits (1991) shows that logs with less than 30 cm of diameter should not be peeled. The results in Table 2 confirm the low recovery rate of these assortments.…”
Section: Discussionmentioning
confidence: 99%
“…Logs are generally selected for veneer production on the basis of diameter, straightness and roundness as these affect the conversion efficiency and the quality of the veneer sheets (Fahey and Willits, 1991;Wiedenbeck et al, 2004). Many species, both hardwood and softwood, are capable of yielding acceptable veneers.…”
Section: Peeling and Slicing To Produce Veneersmentioning
confidence: 99%
“…Many species, both hardwood and softwood, are capable of yielding acceptable veneers. Fast-grown logs often yield veneer with a rougher surface or veneer that splits more easily during handling and are more difficult to glue, thus resulting in higher losses (Fahey and Willits, 1991). Logs are generally selected for veneer production on the basis of diameter, straightness and roundness as these affect the conversion efficiency and the quality of the veneer sheets (Fahey and Willits, 1991;Wiedenbeck et al, 2004).…”
Section: Peeling and Slicing To Produce Veneersmentioning
confidence: 99%
“…All these studies have reported favourable veneer recovery rates and mechanical properties from small logs. Engineered wood products manufactured from veneers recovered from young hardwood plantation logs can exceed the mechanical properties of similar products manufactured from mature-age softwood (e.g., Pinus species) plantation logs (Gaunt et al 2003;De Carvalho et al 2004;Rahayu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The value of logs at the lathe for production of veneer-based engineered wood products is determined by green veneer recovery and utility after drying the green veneer (Fahey and Willlts 1991). Green veneer recovery from log volume is affected by the residual cylindrical peeler core diameter, as well as log dimensions and geometry.…”
Section: Introductionmentioning
confidence: 99%